2018
DOI: 10.1002/2017ja025136
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Temporal Variations of Field‐Aligned Currents and Ground Magnetic Deflections During Substorms

Abstract: Field‐aligned currents (FACs), also known as Birkeland currents, are the agents by which energy and momentum are transferred to the ionosphere from the magnetosphere and solar wind. This coupling is enhanced at substorm onset through the formation of the substorm current wedge. Using FAC data from the Active Magnetosphere and Planetary Electrodynamics Response Experiment and substorm expansion phase onsets identified using the Substorm Onsets and Phases from Indices of the Electrojet technique, we examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 111 publications
4
24
0
Order By: Relevance
“…The delay between driving and the nightside onset is on the order of 30 min. The nightside onsets correspond to enhancements in AE, consistent with substorm onsets, and the Birkeland currents are consistent with event analyses of substorm currents using AMPERE (L. Clausen et al, ; L. B. N. Clausen et al, ; Connors et al, ; Coxon et al, ; Coxon et al, ; Forsyth et al, ; McPherron et al, ; Murphy et al, ). The onsets are preceded by a southward turning of the IMF that coincides with the dayside currents.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The delay between driving and the nightside onset is on the order of 30 min. The nightside onsets correspond to enhancements in AE, consistent with substorm onsets, and the Birkeland currents are consistent with event analyses of substorm currents using AMPERE (L. Clausen et al, ; L. B. N. Clausen et al, ; Connors et al, ; Coxon et al, ; Coxon et al, ; Forsyth et al, ; McPherron et al, ; Murphy et al, ). The onsets are preceded by a southward turning of the IMF that coincides with the dayside currents.…”
Section: Discussionsupporting
confidence: 73%
“…Other studies specifically focused on the development of Birkeland currents with subtorms (cf. Coxon et al, ; Forsyth et al, ; McPherron et al, ) and have shown that auroral substorms closely correlate with intensifications of the nightside R1 and R2 Birkeland currents. Our purpose is to understand the sequence in the development of the global Birkeland current system from a substantial period of quiescence so this analysis is distinct though related to these studies of auroral substorms.…”
Section: Introductionmentioning
confidence: 98%
“…Since auroral hiss is caused by the Cherenkov radiation of low-energy precipitating electrons, we considered the behavior of the upward field-aligned currents (FACs), also known as Birkeland currents, corresponding to soft electron precipitation. Some upward current increase prior to substorm onset was found by Forsyth et al (2018).…”
Section: 1029/2019gl086285mentioning
confidence: 94%
“…Following a southward turning of the IMF, the Region 1 FACs are enhanced and become stronger than the Region 2 FACs, and penetration electric fields occur at low latitudes (Nopper & Carovillano, 1978;Senior & Blanc, 1984). Similarly, following a substorm onset, the increase of the Region 1 FACs is larger than the increase of the Region 2 FACs (Forsyth et al, 2018), and penetration electric fields are observed at low latitudes (Huang, 2009(Huang, , 2012.…”
Section: Discussionmentioning
confidence: 98%